Prevalence of health shocks and the influencing factors: evidence from rural Bangladesh - Rakib, Muntaha (Research in Agriculture Livestock and Fisheries, 2020)
To explore the factors associated with the prevalence of health shocks faced by low income people in rural Bangladesh is the major focus of the paper. This paper uses the country representative data called Bangladesh Integrated Household Survey (BIHS) which covers the period 2015 conducted by International Food Policy Research Institute (IFPRI). A simple Probit regression was performed to explore factors associated with the incidence of health shocks, particularly illness and skipping work due to illness. Several influencing factors of health shock exposure are identified; such as household characteristics, health care access and supply-side indicators such as accessibility to different facilities. The study finds that households prevalence to health shocks and experiences of illness are positively associated with increase in consumption while less educated and less affluent households are more hardly affected by health shocks. Access to medical facilities apart from access to financial markets is among the other major influencing factors of health shock prevalence. The finding of the paper is expected to provide evidence for policy-makers in designing health protection mechanisms and targeting the affected people. Res. Agric., Livest. Fish.6(3): 363-371, December 2019